THE ROLE OF CHARACTER EDUCATION IN PREVENTING VERBAL BULLYING BEHAVIOR BETWEEN STUDENTS AT ELEMENTARY SCHOOL - Diana Putri Ariyanti; Wulan Sutriyani; Syailin Nichla Choirin Attalina (Universitas Majalengka, 2024)
This research comes as bullying becomes an increasingly important issue in Indonesia, particularly in education. Indonesia ranks fifth out of 78 countries in terms of bullying cases. The purpose of this study is to examine the role of character education in preventing verbal bullying behavior among students at SDN 4 Bringin. The study employs a descriptive-qualitative approach with data collection methods encompassing observation, interviews, and documentation. The data analysis process used techniques developed by Miles and Huberman, namely data reduction, data presentation, and conclusion drawing. The results showed that the forms of verbal bullying that often occur in class 3 of SDN 4 Bringin are mocking their friends, calling their parents, and saying harsh words. Factors that influence these actions include children's personality factors, the environment, and mass media. Therefore, the role of character education is important in shaping students' positive attitudes, values, and behaviors. Through the application of values such as honesty, responsibility, cooperation, and tolerance, students can develop a better understanding of the negative impact of verbal bullying behavior. The implementation of character education involves teachers, school parties, and parents to create effective and sustainable character education. Based on the research results, it can be concluded that character education has an important role in preventing verbal bullying behavior at SDN 4 Bringin. The implementation of strong character values and the involvement of teachers and parents will support student development. Therefore, concrete steps need to be taken to strengthen the role of character education in preventing verbal bullying behavior among students in the school environment.